A scoping review of the evidence available for the use of salons as health promotion environments, for the prevention and management of non-communicable diseases in women from different ethnic backgrounds - Kaneri, Prerana; Lima do Vale, Marjorie; Harding, Seeromanie; Molokhia, Mariam (Frontiers in Public Health, 2023)
Introduction: Ethnically diverse women are disproportionately affected by non-communicable diseases; this is associated with socioeconomic factors, underlying health, and behavioural factors such as distrust of mainstream health services. Underpinned by the community capital they harness, hairdressers in the USA have successfully delivered CVD prevention programmes to a wider community than primary care, particularly true for African. American women in disadvantaged areas. Integrating community structures into existing primary care pathways can provide a sustainable process to address inequalities in access to health care. This scoping review aimed to map and summarise the evidence about interventions based in beauty salons that have predominantly targeted ethnically diverse women for noncommunicable disease prevention and management. Specific focus will be given to interrogating formative research phases, community participation, co-development, equity, training and incentivisation of therapists, evaluation and theoretical or conceptual underpinning. Methods: The methodological framework was based on the seminal guidance of Arksey and O’Malley, using the ‘PCC’ (participants, concept, context) structure with incorporation of other relevant materials. The Reach, Effectiveness, Adoption, Implementation, and Maintenance framework was used to explore the potential public health impact. Results: 419 titles and abstracts were screened for relevance, with eight meeting the inclusion criteria (2%), all based in the USA. Two used formative phases to inform intervention development, five studies referred to theoretical or conceptual frameworks and three described evidence of co-development with key stakeholders or experts within the community. Incentivisation was provided to therapists in five of the studies, and to clients in three of the studies. Four of the investigations collated data on socioeconomic circumstance of the target population. Discussion: Literature regarding formative research suggest that this phase is valuable in contributing to sustainability of health initiatives; however, the utility of formative research in the scoped studies was weakly reported upon. Community participation was implicit in each of the scoped studies, yet its application varied considerably. Theoretical and conceptual frameworks were not consistently used, and there was inadequate process evaluation to ensure equitable reach and retention of targeted groups across socioeconomic circumstances. A more concerted effort to address health equity is imperative for future interventions.